Testing for service-led and investment-led hypothesis: evidence from 'Chindia' - Abdul Hamid, Baharom; Habibullah, Muzafar Shah; R. C., Royfaizal (Canadian Center of Science and Education, 2009)
This study examines the meaningful relationship between economic growth, and service sector contribution and domestic investment in two major Asian economies, namely India and China. Autoregressive Distributed Lag (ARDL) bounds testing procedure is employed to analyze the impact of the selected variables namely (1) contribution by the service sector, (2) (4) domestic investment on economic growth and vice versa. The period of interest is 1960-2005 using annual data. The empirical results demonstrate that for the case of India, there is (1) a unidirectional causality from domestic investment to economic growth and (2) from economic growth to services. As for China, only unidirectional causality from services sector to economic growth is detected, while no meaningful relationship was found between domestic investment and economic growth.